The effect of transformational leadership style and work motivation on employee performance at PT Telkom Witel Tangerang BSD - Riris Lestiowati; Sonny Fransisco (Privietlab, 2021)
This study aims to determine the effect of transformational leadership style and work motivation on employee performance. This research is a case study with a quantitative approach. NSData used in this study is primary data collected through a questionnaire using a saturated sample technique. The data analysis technique in this study is some linear analysis using statistical software products and service solutions (SPSS) 26. The results of this study indicate that Transformational Leadership Style and work motivation have a partial effect of simultaneous influence on performance.